COOPERATION AND THE POLITICS OF EMANCIPATION : ARISTOTLE AND MARX - Bielskis, Andrius (Sociologija. Mintis ir veiksmas, 2015)
This article aims to provide an alternative conception of the politics of emancipation against the background of Aristotelian and Marxist theories. It links emancipatory politics with a specific notion of faith as a fundamental feature of being in the world, one enabling the interpellation of dominant ideologies and distorted political power structures. Aristotle’s conception of the zoon politikon is reinterpreted in terms of an intersubjectivity based on human cooperation, and its three essential aspects – symmetry/symmetry, teleology and structures of meaning – are analysed. Once these concepts have been articulated, a philosophical critique of neoliberal capitalism becomes possible: the logic of capital circulation becomes irrational when seen from the viewpoint of intersubjective cooperation, given that capitalism is based on profit maximisation, on subordinating labour to capital, on control over the entire production process through the private ownership of the means of production, and on the commodification of human life. The article ends with a brief account of economic democracy.